PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) DALAM MENINGKATKAN KEAKTIFAN PESERTA DIDIK PADA MATA PELAJARAN IPAS KELAS III SDN 186/I SRIDADI - Aziza Maharani; Barokah, Tetty; Sari, Maya; Putri, Nadia; Risdalina, Risdalina; Destrinelli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve student learning activeness through the implementation of the cooperative learning model Team Games Tournament (TGT) in the subject of Natural and Social Sciences (IPAS) for Grade III students at SDN 186/I Sridadi. The research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 16 third-grade students. Data collection techniques included observation, interviews, and documentation. The results showed that the implementation of the TGT model significantly increased student learning activeness. In Cycle I, student activeness was categorized as "low," with only 12.5% of students actively participating. After improvements were made in Cycle II, the number of active students increased to 87.5%, with overall activeness rated as "good." The TGT model, which integrates elements of games, teamwork, and competition, effectively created an engaging and collaborative learning environment that encouraged student participation. Thus, the TGT model proved effective as an alternative instructional strategy to enhance student engagement in IPAS lessons and other subjects at the elementary level.